2021
DOI: 10.3390/jfmk6040092
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Post-Training Hypotensor Effect in Paralympic and Conventional Powerlifting

Abstract: High blood pressure (HBP) has been associated with several complications and causes of death. The objective of the study was to analyze the hemodynamic responses in Paralympic bench press powerlifting (PP) and conventional powerlifting (CP) before and after training and up to 60 minutes (min) after training. Ten PP and 10 CP athletes performed five sets of five repetition maximal bench press exercises, and we evaluated systolic, diastolic, and mean blood pressure (SBP, DBP, and MBP, respectively), heart rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 35 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…Thus, it appears that the consumption of ibuprofen tends to attenuate anti-inflammatory cytokine IL-10 increases but would not alter leukocyte subset concentrations [ 59 ]. Perhaps an explanation for this is that Paralympic athletes have a greater amount of body musculature involved in strength training, such as the bench press, as mentioned in another study regarding hemodynamic variation in conventional and Paralympic powerlifting athletes, which would explain part of the findings in our study [ 60 ].…”
Section: Discussionmentioning
confidence: 67%
“…Thus, it appears that the consumption of ibuprofen tends to attenuate anti-inflammatory cytokine IL-10 increases but would not alter leukocyte subset concentrations [ 59 ]. Perhaps an explanation for this is that Paralympic athletes have a greater amount of body musculature involved in strength training, such as the bench press, as mentioned in another study regarding hemodynamic variation in conventional and Paralympic powerlifting athletes, which would explain part of the findings in our study [ 60 ].…”
Section: Discussionmentioning
confidence: 67%
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [ 30 , 31 ] investigated the physiological responses in PP. Paz et al [ 30 ] conducted a randomized cross-over trial to explore post-exercise hypotension after two high-intensity resistance-training sessions in a sample of ten national-level PP athletes (aged 26.1 ± 6.9 years; body weight 76.8 ± 17.4 kg).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations